2020
DOI: 10.3390/su13010063
|View full text |Cite
|
Sign up to set email alerts
|

Community Perceptions of Mangrove Ecosystem Services and Their Determinants in the Rufiji Delta, Tanzania

Abstract: Understanding how local communities perceive and depend on mangrove ecosystem services (MES) is important for translating and incorporating their benefits, priorities, and preferences into conservation and decision-making processes. We used focus group discussions, key informant interviews, household questionnaires, and direct observations to explore how local communities in the Rufiji Delta perceive a multitude of MES and factors influencing their perceptions. Sixteen MES were identified by the respondents. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 50 publications
5
22
0
1
Order By: Relevance
“…These ethnic groups represent the indigenous sociocultural groups of the area (Gnansounou et al, 2021), and therefore are more knowledgeable about the degradation of mangroves in the reserve. This concurs with Nyangoko et al, (2021) who found difference in perception in the local use of mangroves in Tanzania with a signi cant variation across ethnic groups.…”
Section: Discussionsupporting
confidence: 91%
“…These ethnic groups represent the indigenous sociocultural groups of the area (Gnansounou et al, 2021), and therefore are more knowledgeable about the degradation of mangroves in the reserve. This concurs with Nyangoko et al, (2021) who found difference in perception in the local use of mangroves in Tanzania with a signi cant variation across ethnic groups.…”
Section: Discussionsupporting
confidence: 91%
“…In total, twenty-one services were identified in the reserve. Mangrove ES reported by interviewees in this study are consistent with those found in many other studies [16,31] with a slight difference in nomenclature. This difference in nomenclature is justified by the fact that there is not to date a unique form of classification of the subcategories of ES [32].…”
Section: Diversity Of Mangrove Es In the Mtbrsupporting
confidence: 92%
“…This difference in nomenclature is justified by the fact that there is not to date a unique form of classification of the subcategories of ES [32]. However, the services recorded in the reserve outnumber the ones reported by [16] and [31] who investigated mangrove ES respectively in Mexico and Tanzania using the same approach. The former reported thirteen mangrove ES while the latter recorded sixteen.…”
Section: Diversity Of Mangrove Es In the Mtbrmentioning
confidence: 99%
“…Similar accounts were reported wherein respondents demonstrate a doubtful knowledge of the medicinal benefits of mangroves (Sulaiman et al 2019;Wahyuni et al 2021). Nyangoko et al (2021) even found out that local inhabitants perceive this benefit as unimportant compared to other provisioning services.…”
Section: Level Of Community Knowledgementioning
confidence: 98%
“…Awareness that mangroves provide one or all of these benefits was documented in several studies (e.g., Dencer-Brown et al 2019;Quevedo et al 2019;Setiyaningrum 2019;Wahyuni et al 2021). Most locals recognize these benefits due to their perceived importance and direct value to human livelihood (Nyangoko et al 2021). Interestingly, a considerable number of surveyed residents were not knowledgeable of mangroves being a source of firewood and charcoal at 24.7%, and construction and fishing materials at 27.9%.…”
Section: Level Of Community Knowledgementioning
confidence: 99%